Ketoconazole-pamam Dendrimer Supramolecular Complex for Prolonged Delivery by In Vitro and In Vivo Studies - KACSO, Irina; BÂLDEA, Ioana; MICLĂUȘ, Maria-Olimpia; MOŢ, Augustin Cătalin; MOLDOVAN, Remus; MARTIN, Flavia (Studia Universitatis Babeș-Bolyai Chemia, 2023)
The current study investigates the potential of the supramolecular complex between the antifungal agent Ketoconazole (KTZ) and PAMAM dendrimer G5 generation to be used as a topically applied antimycotic drug. The new drug-dendrimer formulation was confirmed by combining XRPD, FT-IR and DSC analytical techniques, and presents improved aqueous solubility and delayed in vitro release profile compare to pure KTZ. The biological assays data showed the biocompatibility of the supramolecular complex and improved delivery of the encapsulated KTZ into the superficial layers of skin and mucosa at the mycotic infections site, leading to a better outcome of the infection.